A közelmúlt magyar irodalmi kroatisztikája - Orsolya, Kálecz-Simon (Slavia Centralis, 2020)
The following paper presents the most important tendencies of the studies of Croatian Literature in Hungary. After presenting the new challenges appeared in the 1990s, we draft the portraits of the most important Hungarian professionals of Croatian (Literary) Studies, presenting their most important works, goals and their methodology.
Keywords: Hungary; Croatian studies; literature; Stipan Blažetin; István Fried,; László Heka; István Lőkös; Stjepan Lukač; Zoltán A. Medve; Zoltán Virág